Achieving the Millennium Development Goals : The Role of Infrastructure - Leipziger, Danny; Fay, Marianne; Wodon, Quentin; Yepes, Tito (World Bank, Washington, DC, 2014)
The authors provide an empirical analysis of the determinants of three child-health outcomes related to the Millennium Development Goals: the infant mortality rate, the child mortality rate, and the prevalence of malnutrition. Using data from Demographic and Health Surveys, they go beyond traditional cross-country regressions by exploiting the variability in outcomes and explanatory variables observed within countries between asset quintiles. The authors show the relationships existing between the prevalence of diseases (diarrhea and malnutrition) and mortality. Their findings suggest that apart from traditional variables (income, assets, education, and direct health interventions), better access to basic infrastructure services has an important role in improving child health outcomes. Their analysis of interaction effects between interventions also suggests the importance of combining interventions to meet the Millennium Development Goals.